2000
DOI: 10.1577/1548-8675(2000)020<0119:viwawl>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Walleye Abundance with Lake Size and Recruitment Source

Abstract: We quantified the relationship between lake size and abundance of walleyes Stizostedion vitreum at two life stages, age 0 and adult, in 172 northern Wisconsin lakes. We also determined if the relationship varied with recruitment source (stocked or natural) in order to evaluate the current system of management. For adult walleyes, as estimated by mark-recapture in spring, abundance was linearly related to lake surface area. Age-0 walleye abundance estimated by fall electrofishing catch was also linearly related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
(48 reference statements)
2
51
0
Order By: Relevance
“…Limnologists have developed empirical models that relate various aspects of lake productivity to lake geometric indices. In 172 northern Wisconsin lakes, the surface area explained 59% of the variability in adult walleye (Stizostedion vitreum) abundance (Nate et al, 2000). Ryder (1965) proposed a method to calculate the fish productivity of lakes on the basis of the 'morphoedaphic index' and Khalil (1998) presented a strong positive correlation of fish yield with MEI and DL.…”
Section: Resultsmentioning
confidence: 99%
“…Limnologists have developed empirical models that relate various aspects of lake productivity to lake geometric indices. In 172 northern Wisconsin lakes, the surface area explained 59% of the variability in adult walleye (Stizostedion vitreum) abundance (Nate et al, 2000). Ryder (1965) proposed a method to calculate the fish productivity of lakes on the basis of the 'morphoedaphic index' and Khalil (1998) presented a strong positive correlation of fish yield with MEI and DL.…”
Section: Resultsmentioning
confidence: 99%
“…We compiled data on walleye abundance from the literature (Lyons and Magnuson 1987;Johnson et al 1992b;Mitzner 1992;Beard et al 1997;Carlander 1997;Kershner et al 1999;Nate et al 2000) to compare with walleye abundance in Spirit Lake. Abundance estimates from 63 lakes (age-classes greater than age 0) averaged 27.2 fish/ha, compared with a 3-year average of 196.4 fish/ha (Ն150 mm) in Spirit Lake.…”
Section: Discussionmentioning
confidence: 99%
“…Further, no density-independent characteristics improved the amount of variability explained by walleye growth in each model, which supports our assumption of independence between all variables and our decision to not use inverse prediction as a biologically relevant statistical test (Zar 1984). This may suggest that adult walleye density is not influenced by density-independent characteristics of the lakes themselves; however, Nate et al (2000Nate et al ( , 2001 has shown that increased lake size, percentage of sand and muck bottom substrate, and conductivity have a positive influence on walleye abundance. There are several sources of error in the independent variables that may have accounted for our lack of ability to predict adult walleye density on a regional scale including error associated with the population estimates, timing of the population estimates, and stocking (Ricker 1973;Walters and Ludwig 1981).…”
Section: Figmentioning
confidence: 99%
“…For example, walleye growth has been found to be sexually dimorphic in some lakes (Rawson 1957;Wolfert 1977;Henderson et al 2003) but not in others (Ragan 1976; Roberge et al 1988). In general, densityindependent factors such as climate and lake morphometry are used to explain patterns in walleye growth and population dynamics between lakes (Nate et al 2000). Unfortunately, incorporation of these physical variables has provided little help in resolving the uncertainty associated with predicting regional-scale patterns (Walters and Collie 1988).…”
Section: Introductionmentioning
confidence: 99%